MOTIVASI KERJA, KEPUASAN KERJA, DAN KOMITMEN ORGANISASIONAL KARYAWAN - Steven Gondokusumo; Eddy Madiono Sutanto (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2015)
This study was conducted to determine the effect of work motivation and job satisfaction on organizational commitment. The population amounted to 214 employees and the samples were 145 people. The sampling method was judgment sampling. The analytical method was multiple linear regression. The results indicated that work motivation variable had a positive and significant effect on organizational commitment. Job satisfaction also had a positive and significant influence on organizational commitment. Work motivation and job satisfaction had the same influence on organizational commitment and job satisfaction dominated. The increase in employee motivation was expected to help the company in increasing employee’s job satisfaction that directly affected the commitment of employees.